Answer:
x = 7
Explanation:
First, you can start by subtracting 14x - 49 from both sides to get 0 on the left side:
x^2=14x-49
-(14x - 49) -(14x - 49)
x^2 - 14x + 49 = 0
Now, we can realize that this equation resembles a perfect square trinomial, which would be in the form a^2 - 2ab + b^2. This factors to (a - b)^2. We can say that x^2 corresponds to a^2 and 49 corresponds to b^2. We can wrote two equations to solve for a and b:
a^2 = x^2
a = x
b^2 = 49
b = 7
This means we can factor x^2 - 14x + 49 into (x - 7)^2.
Now we can use the zero product property:
(x - 7)^2 = 0
x - 7 = 0
x = 7